2017
DOI: 10.1093/aob/mcw240
|View full text |Cite
|
Sign up to set email alerts
|

Reduced susceptibility of tomato stem to the necrotrophic fungusBotrytis cinereais associated with a specific adjustment of fructose content in the host sugar pool

Abstract: Background and aims Plant soluble sugars, as main components of primary metabolism, are thought to be implicated in defence against pathogenic fungi. However, the function of sucrose and hexoses remains unclear. This study aimed to identify robust patterns in the dynamics of soluble sugars in sink tissues of tomato plants during the course of infection by the necrotrophic fungus Botrytis cinerea. Distinct roles for glucose and fructose in defence against B. cinerea were hypothesized. Methods We examined sugar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 65 publications
4
46
0
3
Order By: Relevance
“…In the process of pathogen infection a series of genes and pathways are activated, and extensive efforts have been devoted to understanding plant defense signaling pathways (Uppalapati et al ., ). Emerging evidence has shown a causal link between primary metabolism and defense responses to plant pathogens (Bolton, ; Rojas et al ., ; Lecompte et al ., ; Schwachtje et al ., ). In the present study, MTC was demonstrated to be extensively involved in R. solanacearum –tomato interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of pathogen infection a series of genes and pathways are activated, and extensive efforts have been devoted to understanding plant defense signaling pathways (Uppalapati et al ., ). Emerging evidence has shown a causal link between primary metabolism and defense responses to plant pathogens (Bolton, ; Rojas et al ., ; Lecompte et al ., ; Schwachtje et al ., ). In the present study, MTC was demonstrated to be extensively involved in R. solanacearum –tomato interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Using top-down modelling based on the construction of generalised linear models [30], we demonstrate that metabolomics data can be used to accurately predict the measured resistance to various fruit pathogens ( Figure 6A). Besides, through the evaluation of the occurrence of best predictors, our data indicate that soluble sugars, more specifically fructose [42], and defence metabolites are pivotal to predict the resistance to fruit pathogens (Table S1). Clearly, a more global systems biology approach based on a higher level of variation in the conditions (e.g., multiple genotypes or priming treatments, various growth stages of the fruit, several infection points) will shed some light on the underlying mechanisms of fruit-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogen infection also changes the accumulation traits of carbon assimilates (Lecompte et al ). Soluble sugar, starch and NSC were sharply accumulated in diseased FL, moreover, K deficiency significantly aggravates the accumulation of soluble sugar in FL, which is consistent with the high contribution of K deficiency to the content of soluble sugar and starch in FL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, K deficiency also induces accumulation of low‐molecular‐weight compounds in host plants, such as soluble sugars and free amino acids, among others (Hu et al , Hu et al ). These primary metabolites of carbon are readily accessible to pathogens (Marschner , Lecompte et al ) and are easily hijacked by pathogens. By contrast, a sufficient K supply alleviated the membrane lipid peroxidation and increases the exportation of soluble sugar from source leaves (Oosterhuis et al ) and increases the internal competition of a host plant for nutrient resources (Wang et al ).…”
Section: Introductionmentioning
confidence: 99%